Relationship between love addiction, post-traumatic cognitions, and rumination - Gökçen, Gülden; Traş, Zeliha; Yakıcı, Hikmet Beyza y (Journal of Dependence, 2025)
Objective: This study aims to examine the relationships between love addiction, post-traumatic cognitions, and rumination among young adults. Additionally, it investigates whether love addiction differs based on gender and the duration of romantic relationships. Method: The study group consisted of a total of 515 individuals aged between 18 and 35 who were in a romantic relationship (e.g., spouse, partner, dating). Among the participants, 120 were men (23.3%), and 395 were women (76.7%). Data were collected using the Love Addiction Scale, the Post-Traumatic Cognitions Scale, the Interpersonal Mistreatment-Related Rumination Scale, and a Personal Information Form. Results: The present study identified significant differences in love addiction as a function of gender and the duration of romantic relationships. Furthermore, a modest yet statistically significant positive correlation was observed between love addiction scores and both post-traumatic cognitions and rumination related to interpersonal transgressions. Hierarchical regression analysis further demonstrated that rumination on interpersonal transgressions and post-traumatic cognitions served as significant predictors of love addiction. Conclusion: Love addiction is a multifaceted phenomenon influenced not only by relational factors but also by the enduring cognitive consequences of traumatic experiences and persistent rumination on interpersonal failures. These results emphasize the imperative of integrating trauma-informed therapeutic practices and cognitive restructuring techniques focused on diminishing ruminative tendencies into interventions targeting love addiction.